Queering Eve: Imagining Transgender Acceptance in Orthodox Judaism - Maier, Jessie (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2022)
While the Reform and Conservative Jewish movements have made a concerted effort to welcome transgender Jews in the last twenty years, transgender congregants are often shunned by Orthodox rabbis and synagogues in the United States. Studies about Orthodox Judaism’s relationship with transgender identity often focus exclusively on Talmudic justifications for the acceptance or rejection of transgender Jews, ignoring the increasingly sizeable effect that secular politics has on the American Orthodox community. To address this gap in the academic understanding of transgender Jewish issues, this analysis takes a more holistic approach to the issue of transgender acceptance in Orthodox Judaism by (1) assessing the potential for the acceptance of transgender Jews in ultra-Orthodox and Modern Orthodox Jewish communities in the United States using halakhic rulings on intersex and transgender issues and (2) tracing the potential effects of the American political landscape on the Orthodox community’s acceptance of transgender identity.